2017
DOI: 10.1097/sla.0000000000001830
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Clostridium difficile Infection in Mice by Dietary Supplementation With Indole-3-carbinol

Abstract: Objective To determine the therapeutic effects of dietary supplementation on C. difficile infection (CDI). Background With limited treatment options, the rise of Clostridium difficile-associated disease has spurred on the search for novel therapies. Recent data define a role for the aryl hydrocarbon receptor (AHR) and diet-derived AHR ligands in mucosal immunity. We investigated the efficacy of indole-3-carbinol (I3C), a dietary supplement and AHR precursor ligand, in a murine model of CDI. Methods C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
1
35
1
Order By: Relevance
“…We found that the administration of the chemical mixture within broccoli does not mitigate AHR activation. Notably we observe the occurrence of broccoli mediated benefits and AHR activation at relatively low daily doses of I3C (4.64 mg/kg), which is 15–60 fold lower than that used in previous studies (Stoner, Casto et al 2002; Julliard, De Wolfe et al 2016). While heightened doses of I3C may promote intestinal health, they will lead to systemic circulation of AHR ligands that are associated with development of hepatocarcinoma (Stoner, Casto et al 2002; (NTP) 2014).…”
Section: Discussioncontrasting
confidence: 66%
“…We found that the administration of the chemical mixture within broccoli does not mitigate AHR activation. Notably we observe the occurrence of broccoli mediated benefits and AHR activation at relatively low daily doses of I3C (4.64 mg/kg), which is 15–60 fold lower than that used in previous studies (Stoner, Casto et al 2002; Julliard, De Wolfe et al 2016). While heightened doses of I3C may promote intestinal health, they will lead to systemic circulation of AHR ligands that are associated with development of hepatocarcinoma (Stoner, Casto et al 2002; (NTP) 2014).…”
Section: Discussioncontrasting
confidence: 66%
“…Supplementation of a semipurified diet with I3C reduces the severity of C. difficile infection in WT and AhR -/mice, suggesting that the effects of I3C may be mediated by both AhR-dependent and independent mechanisms. 173 At least in WT mice, I3C diet-mediated protection against C. difficile infection was due to increased populations of cecal Treg, ILC3, γδ T cells, and neutrophils before infection. 173 In addition to its protective effect against intestinal pathogenic bacteria, AhR is also involved in resistance to fungi.…”
Section: Ahr and Intestinal Infectionmentioning
confidence: 95%
“…173 At least in WT mice, I3C diet-mediated protection against C. difficile infection was due to increased populations of cecal Treg, ILC3, γδ T cells, and neutrophils before infection. 173 In addition to its protective effect against intestinal pathogenic bacteria, AhR is also involved in resistance to fungi. Administration of IAld, a bacteria-derived AhR ligand, to Candida albicans-infected WT mice induced IL-22 production by colonic NKp46 + cells, which enhanced resistance to fungi.…”
Section: Ahr and Intestinal Infectionmentioning
confidence: 95%
“…These studies, along with the general chemopreventive properties of AHR ligand treatment on gastrointestinal health would suggest that AHR ligands in the diet may protect against opportunistic bacterial infections. Indeed, a recent study demonstrated that dietary I3C can decrease the level of Clostridium difficile induced lethality in mice, in part through activation of the AHR [86]. It will be important to test other AHR ligands in this infection model.…”
Section: Intestinal Challenge Models and Ahr Ligandsmentioning
confidence: 99%